Neuroticism, extraversion and conscientiousness as predictors of the hedonistic lifestyle - Taufik, Taufik; Prihartanti, Ninik; Abd Hamid, Harris Shah (North American Journal of Pyschology, 2019)
The present study aimed to investigate relationships of big five personality traits (openness to experiences, conscientiousness, extraversion, agreeableness, and neuroticism) with the hedonistic lifestyle as well as gender differences in two variables. Participants were students of the Psychology Department at Universitas Muhammadiyah Surakarta, Indonesia. A total of 256 students (165 women and 91 men) were selected based on the simple random sampling. The Indonesian version of the Big Five Personality Inventory Scale and the Hedonistic lifestyle Scale were used in the research. The results indicated that three dimensions of the big five, namely conscientiousness, extraversion, and neuroticism, were significantly correlated with the hedonistic lifestyle. conscientiousness had a greater correlation with the hedonistic lifestyle compared to the extraversion and neuroticism. However, the other two dimensions, namely the openness to experience and agreeableness were not correlated with the hedonistic lifestyle. Meanwhile, female participants showed significantly higher levels of hedonistic lifestyle, neuroticism, and agreeableness than men; however, the conscientiousness was significantly higher in men than women. © NAJP.